Factors Influencing ISO 14001 Firm’s Perceived Environmental Performance in Malaysia - S. Rohati; M.N. Norlida; A.N.S.M. Syed Jamal (ASEAN Journal on Science and Technology for Development, 2016)
The changes in the global environmental conditions have placed great challenges on governments, industries, and societies. Business organizations are often blamed for being the sources of theseenvironmental problems. This study aimed to examine the factors influencing the perceived environmental performance of firms certified under the ISO 14001 in Malaysia. A total of 268 manufacturing companies responded to the questionnaires. In this study, structural equation modeling was applied to test the hypotheses. It was found that the “environmental policy”, “environmental training”, “regulatory stakeholder’s pressures”, and “customer pressures”, influence the firm’s perceived environmental performance in which “customer pressures”, was found to be the dominant factor. The measure of environmental performance was self-reported due to the lack of available data. Therefore, perceived environmental performance was employed for this study which is aperceived measure based on the dimensions of the ISO 14001 definition. This study provided a model to synthesize both internal (environmental policy and environmental training) and external (regulatory stakeholder’s pressure and customer pressures) constructs that influenced a firm’sperceived environmental performance. The empirical results and insights from interviews shed lights on the practitioners as to how to enhance a firm’s environmental performance through green practices.